2015
DOI: 10.1021/acs.biochem.5b00697
|View full text |Cite
|
Sign up to set email alerts
|

Two Loops Undergoing Concerted Dynamics Regulate the Activity of the ASH1L Histone Methyltransferase

Abstract: ASH1L (Absent, Small, or Homeotic-like 1) is a histone methyltransferase (HMTase) involved in gene activation that is overexpressed in multiple forms of cancer. Previous studies of ASH1L’s catalytic SET domain identified an autoinhibitory loop that blocks access of histone substrate to the enzyme active site. Here, we used both NMR and X-ray crystallography to identify conformational dynamics in the ASH1L autoinhibitory loop. Using site-directed mutagenesis we found that point mutations in the autoinhibitory l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 52 publications
(123 reference statements)
3
31
1
Order By: Relevance
“…Molecular dynamics simulations, crystallographic and NMR studies have shown that the NSD1 and ASH1L autoinhibitory loops experience conformational heterogeneity in the absence of nucleosome substrate [127,128]. In none of the observed conformations does the autoinhibitory loop completely open to allow nucleosome binding, suggesting that interaction with nucleosome is required to induce loop opening.…”
Section: Structural Studies Of Nsd Ash1l and Setd2 Set Domains Demonstmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular dynamics simulations, crystallographic and NMR studies have shown that the NSD1 and ASH1L autoinhibitory loops experience conformational heterogeneity in the absence of nucleosome substrate [127,128]. In none of the observed conformations does the autoinhibitory loop completely open to allow nucleosome binding, suggesting that interaction with nucleosome is required to induce loop opening.…”
Section: Structural Studies Of Nsd Ash1l and Setd2 Set Domains Demonstmentioning
confidence: 99%
“…In none of the observed conformations does the autoinhibitory loop completely open to allow nucleosome binding, suggesting that interaction with nucleosome is required to induce loop opening. Nevertheless, conformational dynamics of the loop may be important for facilitating the larger conformational change that must occur upon nucleosome binding [127,128]. Interestingly, the autoinhibitory loop in the crystal structure of the related NSD3 SET domain is disordered [129], further suggesting that autoinhibitory loop dynamics are characteristic of the NSD and related SET domains.…”
Section: Structural Studies Of Nsd Ash1l and Setd2 Set Domains Demonstmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamics of the post‐SET loop are significant, as the loop must move prior to peptide binding or its movement must be induced upon interaction with the substrate. In addition, mutagenesis studies on the corresponding region of ASH1L have suggested that this loop region is not merely a blockade to peptide binding, but rather plays a more complex role in enzymatic activity . As ligands targeting this region of NSD1 would have to bind prior to the peptide binding in order to be effective, it is necessary to understand the dynamics of this loop region.…”
Section: Introductionmentioning
confidence: 99%